Comparative assessment of antibacterial activity of uvaria chamae parts (2010)
Methanolic extracts of the root, stem and leaf of Uvaria chamae were evaluated for their antibacterial activity against Methicillin-Resistant Staphylococcus aureus (MRSA), Staphylococcus aureus, Escherichia coli, Klebsiella spp, Proteus spp, and typed strains E. coli ATCC 25922, S. aureus ATCC 25923 and Pseudomonas aeruginosa ATCC27853 using standard agar diffusion method at 50, 100, 150, 200 and 250 mg/ml. Preliminary phytochemical screening revealed the presence of alkaloids, tannins, flavonoids, cardiac glycosides and cyanogenic glycosides. In general, the stem bark extract inhibited the growth of all the tested organisms with leaf extract showing the least antibacterial activity. The MIC of methanolic stem extract on E. coli, MRSA, Klebsiella spp, Proteus spp, E. coli ATCC 25922, S. aureus ATCC 25923 and P. aeruginosa ATCC 27853 were 5.62, 12.59, 200, 35.48, 28.18, 5.62 and 19.95 mg/ml respectively while that of root extract with the exclusion of Klebsiella spp were 31.62, 10.0, 3.55 2.82, 12.59 and 39.81 mg/ml respectively. Methanolic leaf extract was found to have MIC 200, 19.95, 250, 250, 250 and 200 mg/ml respectively with no MIC value against P. aeruginosa.